IMPROVING STUDENTS' INTEREST IN POETRY WRITING LEARNING BY USING EPIGONAL TECHNIQUE - Triyanto, Triyanto; Sumarwati, Sumarwati; Saddhono, Kundharu (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2018)
This study aims to increase student interest in learning to write poetry with epigonal techniques on students of class VII E SMP Negeri 16 Surakarta academic year 2016/2017. This research is a Classroom Action Research (PTK). This research was started from January 2017-August 2017. Data collection techniques used were observation techniques, interviews, tests, field notes, and document analysis. Data analysis techniques used in this study are descriptive comparative and critical analysis. The results of this study are the application of epigonal techniques which can increase student learning interest in learning to write poetry in class VII E SMP Negeri 16 Surakarta Lesson Year 2016/2017. This is seen in cycle I meeting 1, the percentage of students who were active during apperception 75.17%; attention and concentration 75,86%; and students' enthusiasm and enthusiasm when teachers delivered materials of 78.62%. In the second cycle of meeting 2 there was an increase of the students who were active during the apperception was 84.83%; attention and concentration 86,21%; and students' enthusiasm and enthusiasm when teachers delivered material 86.20%.Key words/phrases: Epigonal Techniques, Poetry Writing, Interests, classroom action research, Indonesian PENINGKATAN MINAT SISWA DALAM PEMBELAJARAN MENULIS PUISI MENGGUNAKAN TEKNIK EPIGONAL AbstrakPenelitian ini bertujuan untuk meningkatan minat siswa dalam pembelajaran menulis puisi dengan teknik epigonal pada siswa kelas VII E SMP 16 Surakarta tahun pelajaran 2016/2017. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK). Penelitian ini dimulai dari Januari 2017-Agustus 2017. Teknik pengumpulan data menggunakan teknik observasi, wawancara, tes, catatan lapangan, dan analisis dokumen. Teknik analisis data yang digunakan dalam penelitian ini adalah deskriptif komparatif dan analisis kritis. Hasil penelitian ini adalah penerapan teknik epigonal dapat meningkatkan minat belajar siswa dalam pembelajaran menulis puisi pada kelas VII E SMP Negeri 16 Surakarta Tahun Pelajaran 2016/2017. Hal ini terlihat pada siklus I pertemuan 1 persentase siswa yang aktif selama apersepsi 75,17%; perhatian dan konsentrasi 75,86%; dankeaktifan dan antusias siswa pada saat guru menyampaikan materi 78,62%. Pada siklus II pertemuan 2 terjadi peningkatan yaitu siswa yang aktif selama apersepsi adalah 84,83%; perhatian dan konsentrasi 86,21%; dankeaktifan dan antusias siswa pada saat guru menyampaikan materi 86,20%.Kata Kunci/frase: teknik epigonal, menulis puisi, minat, penelitian tindakan kelas, bahasa Indonesia.